Temperaturni obrat v hriboviti Sloveniji - Žiberna, Igor (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1999)
The article treats the phenomenon of temperature inversions in the mountainous Slovenia, the types of temperature inversions, their altitudes and disposition over the year. Especially are treated the phenomena of temperature inversions in the Ljubljana and Bovec basins and in the Drava valley.
Keywords: Alpe; Alps; climatology; doline; klimatogeografija; klimatologija; kotline; Slovenia; Slovenija; temperatura; temperaturni obrat